Comparing COVID-19 metaphors in Chinese and English social media with critical metaphor analysis - Xu, Qingshu (Frontiers in Psychology, 2023)
Metaphors extracted from COVID-19-related online texts offer a unique lens for examining how individuals perceive the pandemic. Users from distinct linguistic backgrounds may select varying source domains to discuss COVID-19, with these choices influenced by multiple factors. Utilizing Critical Metaphor Analysis (CMA) theory and employing the Metaphor Identification Procedure VU (MIPVU), this study conducts a comparative analysis of Chinese and English COVID-19-related metaphors derived from social media platforms, specifically Twitter and Weibo. The findings reveal both commonalities and distinctions between the metaphors employed in Chinese and English texts. Commonalities encompass the widespread use of war and disaster metaphors in both sets of texts. Distinctions are characterized by a higher prevalence of zombie metaphors in English texts and classroom metaphors in Chinese texts. These similarities and differences can be attributed to varying socio-historical factors, as well as the active choices of users to express their values and judgments.